On the welfare effects of adverse selection in oligopolistic markets - Marco De Pinto; Laszlo Goerke; Alberto Palermo (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2022)
We consider a principal-agent relationship with adverse selection. Principals pay informational rents due to asymmetric information and sell their output in a homogeneous Cournot-oligopoly. We find that asymmetric information may mitigate or more than compensate the welfare reducing impact of market power, irrespective of whether the number of firms is given exogenously or determined endogenously by a profit constraint. We further show that welfare in a setting with adverse selection may be higher than the maximized welfare level attainable in a world with perfect observability.
Keywords: D43; D82; L51; 330; Adverse Selection; Oligopoly; Welfare